PEMBEKALAN KETERAMPILAN LARI DAN LOMPAT UNTUK ANAK SEKOLAH DASAR NEGERI 067243 MEDAN SELAYANG - Sembiring , Heka Maya Sari Br; Sidabutar, Astina; Samosir , Siska Meliana; Nababan , Yuditia; Tabo , Deiton (PUAN INDONESIA, 2025)
Basic physical skills like running and jumping are vital for elementary students’ development, fitness, and readiness for more advanced sports. However, many students struggle due to a lack of regular training at school. This activity aimed to train running and jumping skills through an active and enjoyable school-based approach. The methods included direct practice, movement demonstrations, and performance evaluations over four sessions. Participants were fourth-grade students at Public Elementary School 067243 Medan Selayang. The results showed improvements in students’ understanding and basic movement abilities, along with greater interest in physical activities. This program demonstrated that well-planned, systematic, and engaging basic motor skill training can positively impact physical activity quality among elementary students. Moreover, it contributed to boosting students’ motivation, interest, and active participation in physical education lessons.